1994
DOI: 10.1007/s004010050056
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of axonal injury after human head trauma using immunocytochemistry for ?-amyloid precursor protein

Abstract: Severe non-missile head injury commonly results in a form of brain damage known as diffuse axonal injury (DAI). The histological diagnosis of DAI is made by silver staining for the presence of axonal retraction balls. This feature takes about 24 h to develop and does not allow for the early histological diagnosis of DAI. We have used immunocytochemistry for the beta-amyloid precursor protein (beta APP) as a marker for axonal injury in formalin-fixed, paraffin-embedded sections of human brain. Axonal beta APP i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…APP immunohistochemistry is almost the method of choice to demonstrate axonal injury in man [7,17,45] and it is increasingly being used in various laboratory models of acute brain injury [25,26,55]. Although a time course of experimental APP immunoreactivity does not appear to have been undertaken, the literature refers to APP-positive axons as being demonstrable by at least 7 days postinjury and in man APP-positive axons have been described in brain tissue both at 28 days [7] and 99 days post-injury [5].…”
Section: Discussionmentioning
confidence: 99%
“…APP immunohistochemistry is almost the method of choice to demonstrate axonal injury in man [7,17,45] and it is increasingly being used in various laboratory models of acute brain injury [25,26,55]. Although a time course of experimental APP immunoreactivity does not appear to have been undertaken, the literature refers to APP-positive axons as being demonstrable by at least 7 days postinjury and in man APP-positive axons have been described in brain tissue both at 28 days [7] and 99 days post-injury [5].…”
Section: Discussionmentioning
confidence: 99%
“…However, brain insult induces an increase of APP transcription and interrupts its transport, resulting in localized accumulation of APP to detectable levels in the form of axonal bulbs. The detection of APP-positive axonal bulbs is an effective tool for the diagnosis of diffuse traumatic axonal injury in forensic practice [2][3][4][5][6][7][8][9]. The detection of axonal bulbs using conventional hematoxylin and eosin (H-E) or silver staining requires a survival time of at least 15-18 h following head injury.…”
Section: Introductionmentioning
confidence: 99%
“…The detection of axonal bulbs using conventional hematoxylin and eosin (H-E) or silver staining requires a survival time of at least 15-18 h following head injury. However, immunostaining for APP can detect axonal bulbs as early as 2-3 h after head injury [2][3][4][5][6][7][8][9]. Moreover, some axonal bulbs can be detected at 35 min [10] or 90 min [11] after head injury depending on the case.…”
Section: Introductionmentioning
confidence: 99%
“…Techniques for the demonstration of injured axons in the brain have undergone considerable development in recent years [40]. A number of immunocytochemical methods have been introduced with the general acceptance, that greatest sensitivity of labeling, both for postmortem diagnosis and in the experimental situation of damaged axons, may be obtained by using immunocytochemistry for -amyloid precursor protein ( -APP) [41,42]. APP, a membrane-spanning glycoprotein, is transported by fast axoplasmic transport, it is located at both the pre-and postsynaptic sites and it accumulates within axonal swellings in TBI very quickly in humans as a result of loss of fast axonal transport [39,40].…”
Section: Neuropathology Of Mtbimentioning
confidence: 99%
“…APP, a membrane-spanning glycoprotein, is transported by fast axoplasmic transport, it is located at both the pre-and postsynaptic sites and it accumulates within axonal swellings in TBI very quickly in humans as a result of loss of fast axonal transport [39,40]. Therefore, -APP has been suggested recently as a marker of choice for detecting any axonal injury in the brain [41]. Examination of -APP-immunostained sections has shown that the evidence and incidence of axonal damage were much more widespread and frequent than were thought to be the case in the past using the classic silver strain techniques [31, 36-38, 41, 42].…”
Section: Neuropathology Of Mtbimentioning
confidence: 99%